Effect of rice-husk as replacement cement on mechanical properties concrete / Mohd Najmudin Helmi Abu Bakar ... [et al.] - Abu Bakar, Mohd Najmudin; Abdul Kudus, Sakhiah; Mustaffa, Nur Kamaliah; Jamadin, Adiza; Abbas, Hasan Ali; Hassan, Rohana; Kamaruddin, Nadia (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
The cost of producing concrete has increased, and its effects on the natural environment have become apparent. The ideal solution is to use agro-waste material instead of cement in concrete. This research aims to determine how well RHA works as a cement substitute. At increments of 5%, 10%, and 15%, rice husk was applied in substitute of cement. Compressive and flexural tests were performed on a 100 mm x 100 mm x 100 mm cube and 100 mm x 100 mm x 500 mm prisms with varying percentages of RHA substitution. Findings show that the highest control sample has a compressive strength of 49.83 MPa while t The compressive strength began to drop at 5% RHA substitution. The compressive strength decreased as the percentage of RHA used increased from 10% to 15%. The flexural strength data shows that the 10% RHA has a maximum of 4.90 MPa. The lowest value is 3.85 MPa, and it is only seen from 5% of RHA. Thus, it can be inferred that an RHA replacement level of 5% in cement yields a tremendous increase in compressive strength.